2018
DOI: 10.1021/acs.jpca.8b08171
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic Coupling in the First Five Electronic States of Dicyanodiacetylene Radical Cation

Abstract: We examine vibronic coupling in the first five electronic states (X̃2Πg–Ã2Πu–B̃2Σg +–C̃2Σu +–D̃2Πg–Ẽ2Πu) of dicyanodiacetylene radical cation (C6N2 •+) in this article. Prompted by the prediction of its existence in the astrophysical environment, the vibronic band structure of these electronic states of C6N2 •+ has been probed in spectroscopic measurements in laboratory by various groups. Inspired by numerous experimental data, we undertook the task of investigating topographical details of electronic potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…However, the description of the quasi‐diabatic basis is not unique for a poly‐atomic system except for the diatomic case. Therefore, several prescriptions have been suggested in the literature [19,36–60] to construct the quasi‐diabatic electronic PESs. In the present study, we have employed the ab initio procedure to construct them as suggested by Werner and coworkers [19] .…”
Section: Resultsmentioning
confidence: 99%
“…However, the description of the quasi‐diabatic basis is not unique for a poly‐atomic system except for the diatomic case. Therefore, several prescriptions have been suggested in the literature [19,36–60] to construct the quasi‐diabatic electronic PESs. In the present study, we have employed the ab initio procedure to construct them as suggested by Werner and coworkers [19] .…”
Section: Resultsmentioning
confidence: 99%
“…From the simplistic assumption, one may calculate the one‐dimensional tunneling rate by the semi‐classical theory using the Wentzel–Kramers–Brillouin (WKB) approximation, which is sensible and yet overestimating the experiment 53,116,120,121 . As a matter of fact, tunneling dynamics of phenol has been subject to many high‐level dynamic calculations for recent years 9,42,44,51,59,62–67,70,71,74,75 . For instance, Guo and colleagues reported that the OH tunneling rate of phenol calculated on the full‐dimensional potential energy surfaces does not reproduce the experiment without the consideration of the geometric phase which is inevitable in the nonadiabatic transition where the reactive fluxes encircles the conical intersection 62–64,74 .…”
Section: The Tunneling Dissociation Of the Oh Bond In The S1 State O...mentioning
confidence: 99%
“…The πσ*‐mediated photochemistry, in this aspect, is quite unique as it gives the rational explanation for the ultrafast nonradiative transitions of many heteroaromatic molecular systems upon the electronic excitations, which are often relevant to the photochemical or photobiological activities 6,19–38 . As a matter of fact, spectroscopic and dynamic studies on heteroaromatic systems including phenols, 9,12,39–75 thiophenols, 10–12,76–97 anisoles, 98–102 thioanisoles, 5,103–115 or many others are vast in terms of their diversities and detailed dynamic features. Herein, we focus on the H‐atom detachment reactions of phenols and thiophenols especially in terms of the state‐specific tunneling rate constants.…”
Section: Introductionmentioning
confidence: 99%